Efektifitas Pelaksanaan Program Keluarga Harapan (PKH) di Kelurahan Gunung Sarik Kecamatan Kuranji Kota Padang Sumatera Barat - Wulandari, Tri Novia; Chandra, Dedek; Ramadhan, Risky (Lembaga Yasin AlSys, 2024)
The Family Hope Program (PKH) has been running since 2011. PKH aims to break the chain of poverty, and improve the quality of human resources through education and health. PKH is also one of the social assistance programs relied on by the government through various new policies to ease the burden on PKH participants. The focus of the problem to be achieved in this study is how effective the Family Hope Program (PKH) is. The methodology used in this study is quantitative descriptive by collecting data using observations, interviews, and questionnaires. The data sources obtained include primary and secondary data. The results of research in the field show that PKH in Mount Sarik is not effective in its implementation. This is influenced by several inhibiting factors such as data, errors in data collection and determination of recipients, low awareness of PKH participants, and unproductive use of funds.